EFFECT OF USING YOUTUBE AS A TEACHING MEDIA ON THE STUDENTS’ LISTENING SKILLS - Adam, Adam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
The study aimed to assess the impact of YouTube on eighth-grade students' listening skills at SMP Negeri 58 Batam. Conducted as an experimental research, the study included 114 students from the 2022/2023 academic year. The experimental group utilized YouTube videos for listening practice, while the control group relied on audio alone. A pre-test was administered to all students, followed by treatment using YouTube videos and a post-test. Quantitative analysis revealed a significant improvement in the experimental group, as indicated by paired scores with a p-value of 0.000 (0.05), leading to the rejection of the null hypothesis. The findings suggest that YouTube videos effectively enhance students' listening abilities, highlighting the platform's potential as an educational tool for language acquisition in the eighth-grade classroom at SMP Negeri 58 Batam.